Prevalence of substance use and its associated risk factors amongst secondary school students aged 12 to 17 years in Mzuzu, Malawi - Banda, Zondiwe (Department of Psychiatry and Mental Health, 2024)
Background The use of alcohol and other drugs (AODs) among adolescents has emerged as an increasing public health concern globally and requires an urgent response in low- and middle-income countries (LMICs), particularly in Sub-Saharan Africa, where AOD use is on the rise. Recent systematic reviews of regional evidence have estimated that approximately 40% of adolescents use alcohol or other drugs. This translates to a burden of Disability Adjusted Life Years (DALYs) 2.5 times higher than has been seen in high-income countries. To date, very few studies have investigated the prevalence of AOD use among adolescent school learners in Mzuzu, Malawi. As a result, little is known about the factors that may place these adolescents at increased risk of AOD use. This study therefore endeavours to address these gaps. Methods 421 adolescent school learners aged between 12 and 17 years were recruited in this crosssectional study. Following individual informed assent and parental consent, a self-administered questionnaire was administered to secondary school learners to estimate the prevalence of alcohol and drug use in two public secondary schools within the city of Mzuzu, Malawi. Sociodemographic characteristics of all learners, their household members as well as levels of exposure to victimisation and social support were investigated as factors which may influence alcohol and drug use amongst the sample. Means and proportions were used to describe sociodemographic data as well as the prevalence of lifetime alcohol and drug-use. Unadjusted and adjusted associations between risk factors and lifetime alcohol and drug-use were also explored. Only variables that were significant in unadjusted logistic regression models were included in the final adjusted regression model. The findings are presented in the form of odds ratios (ORs) with 95% confidence intervals (CIs). Results The prevalence of lifetime alcohol-use was 17.1% (n=72) across the sample of secondary school learners. A lower prevalence rate of drug-use was found across the sample, with 7.1% (n=30) of learners reporting any prior use of drugs. In adjusted models, being male, school grade level, attending religious services, sleeping arrangements in the household, household ability to meet subsistence needs, tobacco and alcohol-use by other household members were found to be significantly associated with lifetime alcohol use. In the adjusted models for lifetime drug-use, being male, school grade level, living in a single parent household, sleeping arrangements and alcohol-use and drug-use among household members were found to be significant predictors of drug-use among the sample of learners. Conclusion Results from the study show that alcohol and drug-use are prevalent among adolescent school learners in Mzuzu, Malawi and are associated with several socio-demographic and household factors which place learners at increased risk. This illustrates that AOD use is an issue of concern amongst adolescents in Malawi. There is a need for larger studies to be conducted on AOD use among adolescents in Malawi to generate nationally representative data which would help inform the development and implementation of comprehensive services for the treatment and prevention of alcohol and other drug (AOD) use among adolescent school learners in Malawi.